Cellular Automata Study of the Combined Effects of Passive Film Breakdown and Repassivation on Metastable Pits on Sputtered Nanocrystalline Stainless Steel. Issue 4 (1st January 2019) - Liu, Rui; Li, Tianshu; Liu, Li; Cui, Yu; Oguzie, Emeka E.; Li, Ying; Wang, Fuhui
Abstract : The growth of metastable pits on sputtered nanocrystalline stainless steel (NCss) was simulated by a cellular automata technology. Pit morphologies, passive film breakdown, and the metal cation concentration inside the metastable pit during its growth were analyzed. The combined effects of passive film breakdown and repassivation hindered metastable pit growth on the NCss, even though their isolated effects may vary significantly. The calculated values of the critical pitting temperature are shown to be statistically distributed because of the difficulty of passive film breakdown, repassivation, and the metastable/stable pitting transition.